Implementation of Metaverse-Based Virtual Reality Technology in Archieving Subjects in Vocational High Schools - Basuki, Andi; Churiyah, Madziatul; Dharma, Buyung Adi; Arief, Mohammad; Sakdiyyah, Dewi Ayu (Universitas Ahmad Dahlan, 2023)
Background: The problem that occurs to the participants is that the learning media used in the learning process is currently not up to date, so that technological updates are needed to improve the quality of learning. However, to facilitate learning through the integration of the latest technology requires various teacher competencies, namely knowledge, attitudes and skills. Contribution: The contribution of this program is that the community service to conduct training and mentoring activities on how to develop metaversal-based virtual reality learning media to improve the quality of teachers at state vocational high school 1 Ngawi. Method: This service is carried out through five stages of activity, including analysis of field needs, manufacture of virtual reality products, early socialization, provide assistance and evaluation of the results of using virtual reality. Results: The result of this service activity is that the trainees understand the steps for developing learning media with virtual reality technology. This is based on the results of evaluating the achievement of training and mentoring programs involving 27 participants showing that based on the aspects of convenience, usefulness, attractiveness, and satisfaction, an average score of 92% is obtained. Conclusion: The conclusion of this program is that the metaverse-based virtual reality learning media that was introduced to the participants was very easy to apply, useful, interesting, and the participants were satisfied with the training provided